2016
DOI: 10.1038/eye.2016.189
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125b promotes tumor growth and suppresses apoptosis by targeting DRAM2 in retinoblastoma

Abstract: Purpose It is known that microRNAs (miRNAs) are a class of small, noncoding RNAs that act as key regulators in various physiological and pathological processes. However, the regulatory mechanisms involving miRNAs in retinoblastoma (RB) remain largely unknown. The miRNA miR-125b is dysregulated in various human cancers such as breast cancer, human hepatocellular carcinoma, ovarian cancer, and colorectal cancer. However, the significance of miR-125b in RB has not been sufficiently investigated. Our objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…In RB and GMB, miR is significantly upregulated, and then it apparently suppresses DRAM2, p53, and P38. 15,16,65 DRAM2 is a crucial component of the p53 signaling pathway, and the induction of autophagy by DRAM is a potential mechanism contributing to cell death. DRAM2 encodes a transmembrane lysosomal protein that is thought to play a key role in autophagy initiation, and the autophagy induced by DRAM2 is an underlying mechanism of p53-mediated cell death.…”
Section: Upregulation Of Mir-125b In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In RB and GMB, miR is significantly upregulated, and then it apparently suppresses DRAM2, p53, and P38. 15,16,65 DRAM2 is a crucial component of the p53 signaling pathway, and the induction of autophagy by DRAM is a potential mechanism contributing to cell death. DRAM2 encodes a transmembrane lysosomal protein that is thought to play a key role in autophagy initiation, and the autophagy induced by DRAM2 is an underlying mechanism of p53-mediated cell death.…”
Section: Upregulation Of Mir-125b In Cancermentioning
confidence: 99%
“…DRAM2 encodes a transmembrane lysosomal protein that is thought to play a key role in autophagy initiation, and the autophagy induced by DRAM2 is an underlying mechanism of p53-mediated cell death. 15,65 Both p53 and p38MAPK are direct target genes of miR-125b, and p53 is known to activate the apoptotic pathway, while p38MAPK can induce mitochondrial apoptosis. 16, 66 Zheng et al reported that miR-125b expression was significantly higher in poorly differentiated NSCLC cells with high metastatic potential and that it reduced the level of TP53INP1.…”
Section: Upregulation Of Mir-125b In Cancermentioning
confidence: 99%
“…Given the established role played by miRNAs in retinal development and survival, 1 , 2 as well as in a growing number of distinct diseases, 7 10 , 12 , 14 , 15 , 19 , 22 , 39 , 40 we hypothesized that alterations in miRNA expression might contribute to the molecular mechanisms involved in the physiopathology of RP. To provide experimental evidence to support the possible association between miRNA expression and retinal degeneration, miRNA expression profile in retinas from the rd10 RP mouse model 27 29 and C57BL/6J wild-type mice were compared by microarray and RT-qPCR analysis in the early stages of retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a growing list of miRNAs that are known to be differentially expressed in retinal disorders in humans and in animal models, including miR-9, miR-34a, miR-125b, and miR-155 in macular degeneration, 18 , 19 miR-146a and miR-195 in diabetic retinopathy, 20 , 21 and miR-125a and miR-17 in retinoblastoma. 22 , 23 In addition, a group of antiapoptotic miRNAs (miR-155, miR-146a, and miR-29b) was found to be differentially expressed during the chronic cell death stage in canine models of retinal degeneration. 24 Furthermore, a common pattern of aberrantly expressed miRNAs was described in four murine models of RP where miR-1, miR-133, and miR-142 were upregulated despite different genes ( Rho and Rds ) and inheritance patterns being involved.…”
mentioning
confidence: 99%
“…For instance, miR-124 and miR-34a act as tumor suppressors 8,9 while miR-125b functions as a tumor promoter. 10 The carcinogenic role of miR-224-3p has also been identified in human cancer. Although the involvement of miR-224-3p in the progression of retinoblastoma remains unknown, ectopic expression of miR-224-3p has been detected in high-risk human papillomavirus (HPV)-positive cervical cancer cells, and its overexpression has been proven to inhibit autophagy in HPV-infected cells.…”
mentioning
confidence: 99%